Adaptive fault tolerant control for trajectory tracking of a quadrotor helicopter. (August 2018) - Li, Min; Zuo, Zongyu; Liu, Hao; Liu, Cunjia; Zhu, Bing
In this paper, an adaptive fault tolerant controller based onL 1 control is developed and applied to the trajectory tracking for a quadrotor helicopter. Both multiplicative and additive actuator faults are considered. The proposed design is based on nonlinear feed-forward compensations and a typical nonlinear quadrotor model with uncertain inertial parameters and external disturbances. TheL 1 adaptive control design is slightly modified to adapt with the position and the attitude error dynamics. The proposed adaptive controller yields uniformly verifiable bounds on the transient and the steady-state tracking error for any designated bounded reference trajectory. In the presence of fast adaptation, the adaptive controller compensates for actuator fault and disturbances in a particular frequency range. Finally, simulation results are included to validate the effectiveness of the proposed design.